Method for producing hydrogenated random copolymer

By using hydrogenated random copolyester that controls Mooney stress relaxation ratio and Mooney viscosity in the rubber tire material, the problems of inconvenient treatment and insufficient durability of hydrogenated random copolyester in the prior art are solved, and efficient production and good durability are achieved.

JP7650632B2Active Publication Date: 2025-03-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020161957
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-28
Publication Date
2025-03-25
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

The existing hydrogenated random copolyester is inconvenient to process and lacks durability when preparing rubber tire materials, resulting in low processing efficiency and poor durability of tire sheets.

Method used

By copolymerizing the aromatic ethylene vinyl compound and conjugated diene compound and then carrying out a hydrogenation reaction, the hydrogenated Mooney stress relaxation ratio and Mooney viscosity are controlled within a specific range to improve the production efficiency and durability of hydrogenated random copolyesters.

Benefits of technology

The efficient production and good handling of hydrogenated random copolyester are achieved, while improving its durability and wear resistance in rubber tire materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650632000001
    Figure 0007650632000001
  • Figure 0007650632000002
    Figure 0007650632000002
  • Figure 0007650632000003
    Figure 0007650632000003
Patent Text Reader

Abstract

To provide a hydrogenated random copolymer which has excellent productivity and processability, and moreover when, for example, made into a tire tread, has excellent abrasion resistance.SOLUTION: A method for producing a hydrogenated random copolymer comprises: a polymerization step of polymerizing an aromatic vinyl compound and a conjugated diene compound to obtain a polymer; and a hydrogenation reaction step of performing a hydrogenation reaction by adding hydrogen to the obtained polymer to obtain a hydrogenated random copolymer. In the hydrogenation reaction step, Mooney stress relaxation at 100°C of the obtained hydrogenated random copolymer is adjusted to 0.85 or more to less than 1.05 relative to Mooney stress relaxation at 100°C of the polymer before hydrogenation and, in the hydrogenation reaction step, Mooney viscosity at 100°C of the obtained hydrogenated random copolymer is adjusted to 80 to 200.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a hydrogenated random copolymer, a method for producing a crumb, a method for producing a veil, and a method for producing a pneumatic tire. [Background technology]

[0002] With the future spread of autonomous driving technology, there is a demand for reducing the frequency of tire replacement, i.e., improving tire durability. In order to improve tire durability, it is necessary to improve the wear resistance of tire materials. For example, Patent Document 1 discloses an improvement in the wear resistance of tire materials by using a polymer containing an ethylene structure in a tire tread.

[0003] As a method for obtaining a polymer containing an ethylene structure, for example, a method of adding hydrogen to a conjugated diene polymer having a butadiene structural unit in the chain can be mentioned. For example, Patent Document 1 discloses a method for obtaining a copolymer having an ethylene structure by hydrogenating a styrene-butadiene copolymer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6004081 Summary of the Invention [Problem to be solved by the invention]

[0005] However, as described in Patent Document 1, hydrogenated polymers have insufficient processability when used in tire compounds, and improvements are required. In Patent Document 1, the processability when used in tire compounds is evaluated using adhesion to rolls as an index. In general, the evaluation of the adhesion of a polymer to rolls also correlates with the evaluation of productivity when producing the polymer. Specifically, hydrogenated polymers with low adhesion tend to produce crumbs with low adhesion generated in the steam stripping process during production, which are fine and cause a decrease in dehydration efficiency in the subsequent dehydration process, leading to an increase in the moisture content in the product.

[0006] In Patent Document 1, the processability when forming a tire compound is improved by blending two types of polymers, a high molecular weight hydrogenated polymer and a low molecular weight hydrogenated polymer, but the process is complicated because the high molecular weight hydrogenated polymer and the low molecular weight hydrogenated polymer are produced separately.

[0007] Therefore, there is a demand for an improvement in the productivity in producing hydrogenated polymers, specifically, a technology capable of controlling the particle size of crumbs in the steam stripping process.

[0008] Therefore, an object of the present invention is to provide a hydrogenated random copolymer which is excellent in productivity and processability, and further, has excellent abrasion resistance when made into, for example, a tire tread. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above problems and have found that a hydrogenated random copolymer obtained by a specific production method has excellent productivity and processability, and further has excellent abrasion resistance when made into, for example, a tire tread, and have thus completed the present invention.

[0010] That is, the present invention relates to the following. [1] a polymerization step of polymerizing an aromatic vinyl compound and a conjugated diene compound to obtain a polymer; and a hydrogenation reaction step of adding hydrogen to the obtained polymer to obtain a hydrogenated random copolymer, In the hydrogenation reaction step, the Mooney stress relaxation at 100°C of the resulting hydrogenated random copolymer is 0.85 or more and less than 1.05 relative to the Mooney stress relaxation at 100°C of the polymer before hydrogenation; A method for producing a hydrogenated random copolymer, wherein the hydrogenated random copolymer obtained in the hydrogenation reaction step has a Mooney viscosity at 100° C. of 80 or more and 200 or less. [2] The method for producing a hydrogenated random copolymer according to [1], further comprising a step of reacting the polymer obtained in the polymerization step with a coupling agent and / or a modifier. [3] The method for producing a hydrogenated random copolymer according to [1] or [2], wherein in the hydrogenation reaction step, a total hydrogenation rate of the obtained hydrogenated random copolymer is 50% or more and 95% or less. [4] The method for producing a hydrogenated random copolymer according to any one of [1] to [3], wherein in the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney stress relaxation at 100° C. of 0.2 to 0.6. [5] a polymerization step of polymerizing an aromatic vinyl compound and a conjugated diene compound in a solvent to obtain a polymer solution; a hydrogenation reaction step of adding hydrogen to the obtained polymer solution to perform a hydrogenation reaction to obtain a hydrogenated random copolymer solution; and removing the solvent from the obtained hydrogenated random copolymer solution to obtain hydrogenated random copolymer crumbs having a median diameter (D50) of 6 mm or more and less than 15 mm. In the hydrogenation reaction step, the Mooney stress relaxation at 100°C of the resulting hydrogenated random copolymer is 0.85 or more and less than 1.05 relative to the Mooney stress relaxation at 100°C of the polymer before hydrogenation; A method for producing crumbs, wherein the hydrogenated random copolymer obtained in the hydrogenation reaction step has a Mooney viscosity at 100° C. of 80 or more and 200 or less. [6] [5] Obtaining crumbs by the manufacturing method described in [5]; and compressing the resulting crumb to obtain a bale. [7] A step of obtaining a hydrogenated random copolymer by the production method according to any one of [1] to [4]; a step of mixing the obtained hydrogenated random copolymer with a plasticizer component and a filler component to obtain a rubber composition; and a step of molding the obtained rubber composition to obtain a pneumatic tire. Effect of the Invention

[0011] According to the present invention, there can be provided a hydrogenated random copolymer which is excellent in productivity and processability, and further, which is excellent in abrasion resistance when made into, for example, a tire tread. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. It should be noted that the following embodiment is merely an example for explaining the present invention, and the present invention is not limited to the following embodiment. The present invention can be practiced with appropriate modifications within the scope of the gist thereof.

[0013] [Method for producing hydrogenated random copolymer] The method for producing the hydrogenated random copolymer of the present embodiment includes the steps of: a polymerization step of polymerizing an aromatic vinyl compound and a conjugated diene compound to obtain a polymer; and a hydrogenation reaction step of adding hydrogen to the obtained polymer to obtain a hydrogenated random copolymer, In the hydrogenation reaction step, the Mooney stress relaxation at 100°C of the resulting hydrogenated random copolymer is 0.85 or more and less than 1.05 relative to the Mooney stress relaxation at 100°C of the polymer before hydrogenation; In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100° C. of 80 or more and 200 or less.

[0014] The hydrogenated random copolymer obtained by such a production method is excellent in productivity and processability, and further, when made into, for example, a tire tread, it is excellent in abrasion resistance.

[0015] The mechanism by which the hydrogenated random copolymer obtained by such a production method exhibits the above-mentioned effects is not clear, but the present inventors presume it as follows. In the hydrogenation reaction step, by controlling the Mooney viscosity at 100 ° C of the obtained hydrogenated random copolymer and the Mooney stress relaxation ratio at 100 ° C of the random copolymer before and after hydrogenation within an appropriate range, for example, when producing a hydrogenated random copolymer preferable as a component of a rubber composition for tires, the crumb particle size is not too fine and excellent crumb dehydration efficiency is shown. It is presumed that such an effect can be achieved by controlling the rate of change in the Mooney stress relaxation at 100 ° C of the random copolymer before and after hydrogenation within a specific range, allowing a viscous component effective in enlarging the crumb particle size to remain.

[0016] (Structure of hydrogenated random copolymer) The hydrogenated random copolymer obtained by the production method of this embodiment is, for example, a hydrogenated random copolymer having constituent units based on an aromatic vinyl compound and constituent units based on a conjugated diene compound, in which some of the constituent units based on the conjugated diene compound are hydrogenated, and has a Mooney viscosity at 100°C of 80 or more and 200 or less, and a ratio of Mooney stress relaxation at 100°C before and after hydrogenation (after hydrogenation / before hydrogenation) of 0.85 or more and less than 1.05. The hydrogenated random copolymer is a copolymer in which hydrogen is added to the double bond moieties in the conjugated diene moieties, so that some or all of the conjugated diene moieties are converted to ethylene moieties, and the content of ethylene moieties can be increased by increasing the total hydrogenation rate.

[0017] In the case of hydrogenated random copolymers, the ethylene portion is defined as a portion in which hydrogen has been added to both ends of the main chain of a conjugated diene compound that form a polymer chain (for example, 1,4 bonds in a polymer in which 1,3-butadiene is used as a monomer); the ethylene portion does not include portions in which hydrogen has been added to other forms (for example, 1,2 bonds (vinyl bonds) in a polymer in which 1,3-butadiene is used as a monomer).

[0018] The aromatic vinyl compound used in the present embodiment is not particularly limited, but examples thereof include styrene, α-methylstyrene, 1-vinylnaphthalene, 3-vinyltoluene, ethylvinylbenzene, divinylbenzene, 4-cyclohexylstyrene, 2,4,6-trimethylstyrene, etc. These may be used alone or in combination of two or more kinds, but among these, styrene is particularly preferred from the viewpoint of practical aspects such as easy availability of monomers.

[0019] The conjugated diene compound used in the present embodiment is not particularly limited, but examples thereof include 1,3-butadiene, isoprene, 1,3-pentadiene, 2,3-dimethylbutadiene, 2-phenyl-1,3-butadiene, 1,3-hexadiene, etc. These may be used alone or in combination of two or more kinds, but among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred, from the viewpoint of practical aspects such as easy availability of monomers.

[0020] In this embodiment, the term "hydrogenated random copolymer" means that the content of chains in which 8 or more structural units derived from aromatic vinyl compounds are consecutive (hereinafter also referred to as "long chain ratio") is 10% by mass or less based on the total structural units derived from aromatic vinyl compounds. If the long chain ratio exceeds 10% by mass, fuel economy tends to deteriorate. Here, the long chain ratio was measured for the first polymer using deuterated chloroform as a solvent. 1 In the H-NMR spectrum, it can be calculated as the ratio of the integral value in the range (a) to the sum of the integral values ​​in each of the following chemical shift ranges (a) to (c). For example, if the aromatic vinyl is styrene, the ratio of the integral value in the range (a) to the sum of the integral values ​​in each of the ranges (a) to (c) is calculated, and the ratio of styrene can be calculated by multiplying this value by 2.5. This makes it possible to grasp the state of the chain of structural units derived from aromatic vinyl compounds. (a) Aromatic vinyl compounds with 8 or more chains: 6.00≦S<6.68 (b) Aromatic vinyl compound chains 2-7: 6.68≦S<6.89 (c) Aromatic vinyl compound short chain: 6.89≦S≦8.00

[0021] In the method for producing the hydrogenated random copolymer of the present embodiment, in the hydrogenation reaction step, it is preferable to introduce a branched structure into the polymer in order to control the Mooney viscosity at 100°C of the resulting hydrogenated random copolymer and the ratio of the Mooney stress relaxation of the random copolymer before and after hydrogenation (after hydrogenation / before hydrogenation) within specific ranges. In the case of a linear polymer, the stress relaxation value tends to decrease due to hydrogenation, but by making the polymer into a structure branched into three or more branches, the decrease in Mooney stress relaxation due to hydrogenation can be suppressed, and the stress relaxation ratio can be easily controlled within a certain range.

[0022] The more branches are introduced into the polymer, the less the Mooney stress relaxation is reduced, but in order to control the ratio of the Mooney stress relaxation of the random copolymer before and after hydrogenation (after hydrogenation / before hydrogenation) within a specific range, the lower limit of the number of branches introduced into the polymer is preferably 4 or more, more preferably 6 or more, and even more preferably 8 or more. The upper limit of the number of branches introduced into the polymer is preferably 14 or less, more preferably 12 or less, and even more preferably 10 or less.

[0023] In addition, the method for producing the hydrogenated random copolymer of the present embodiment preferably further comprises a step of reacting the polymer obtained in the polymerization step with a coupling agent. Reacting the polymer with a coupling agent having a functional group to form a modified branched polymer is preferable from the viewpoints of braking performance and wear resistance.

[0024] Specific examples of such coupling agents include, but are not limited to, alkoxysilane compounds such as tetramethoxysilane.

[0025] In the method for producing the hydrogenated random copolymer of this embodiment, the hydrogenated random copolymer obtained in the hydrogenation reaction step has a Mooney viscosity at 100° C. of 80 or more and 200 or less.

[0026] In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100°C of 80 or more, and therefore has excellent abrasion resistance when used as a rubber composition. In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100°C of preferably 95 or more, more preferably 110 or more, and even more preferably 125 or more.

[0027] In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100° C. of 200 or less, and therefore has excellent processability when made into a rubber composition. In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100° C. of preferably 185 or less, more preferably 170 or less, and even more preferably 155 or less.

[0028] In the hydrogenation reaction step, examples of the method for controlling the Mooney viscosity at 100°C of the hydrogenated random copolymer obtained within the above-mentioned specific range include methods for controlling the amount of polymerization initiator or modifier added, the composition ratio of the aromatic vinyl compound and the conjugated diene compound, the amount of 1,2-vinyl bonds, the weight average molecular weight, the total hydrogenation rate, etc. Specifically, for example, when the amount of polymerization initiator or modifier added is increased, the Mooney viscosity of the hydrogenated random copolymer tends to decrease.

[0029] Furthermore, for example, increasing the weight average molecular weight of the hydrogenated random copolymer tends to increase the Mooney viscosity at 100°C of the hydrogenated random copolymer, and conversely, decreasing the weight average molecular weight of the hydrogenated random copolymer tends to decrease the Mooney viscosity at 100°C of the hydrogenated random copolymer.

[0030] Specifically, when the weight average molecular weight of the hydrogenated random copolymer is set to 360,000, for example, when the proportion of aromatic vinyl monomer in the hydrogenated random copolymer is 20 mass% and the amount of 1,2-vinyl bonds in the conjugated diene compound is 20 mol%, the Mooney viscosity at 100 ° C. can be controlled to 80 or more by setting the total hydrogenation rate to 65% or less. Also, for example, when the weight average molecular weight is set to more than 360,000, the Mooney viscosity at 100 ° C. of the hydrogenated random copolymer tends to increase, so it is preferable to lower the total hydrogenation rate of the hydrogenated random copolymer to 50% or less. Conversely, when the weight average molecular weight of the hydrogenated random copolymer is set to less than 360,000, the Mooney viscosity at 100 ° C. of the hydrogenated random copolymer tends to decrease, so it is preferable to increase the total hydrogenation rate of the hydrogenated random copolymer to 70% or more.

[0031] For example, in the case of a hydrogenated random copolymer, when the mass ratio of the aromatic vinyl monomer is 16% by mass, if the amount of 1,2-vinyl bonds in the conjugated diene compound is set to 19 mol% and the weight average molecular weight is set to 1,060,000 or less, the Mooney viscosity at 100°C can be controlled to 200 or less by setting the total hydrogenation rate to 48% or less. For example, in the case of a hydrogenated random copolymer, when the mass ratio of the aromatic vinyl monomer is greater than 16% by mass, the Mooney viscosity at 100°C tends to increase, so it is preferable to reduce the weight average molecular weight to 860,000 or less. For example, in the case of a hydrogenated random copolymer, when the mass ratio of the aromatic vinyl monomer is reduced, the Mooney viscosity at 100°C tends to decrease, so it is preferable to increase the total hydrogenation rate to 70% or more.

[0032] In the present embodiment, the Mooney viscosity at 100° C. of the hydrogenated random copolymer is measured by the method described in the Examples section below.

[0033] In the method for producing the hydrogenated random copolymer of this embodiment, the ratio of Mooney stress relaxation at 100° C. before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) is 0.85 or more and less than 1.05.

[0034] By making the ratio of the Mooney stress relaxation at 100°C before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) 0.85 or more, for example, when producing crumbs of the hydrogenated random copolymer, the particle size of the crumbs in the steam stripping process becomes large, and production stability is excellent. From the same viewpoint, the ratio of the Mooney stress relaxation at 100°C before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) is preferably 0.87 or more, more preferably 0.90 or more, and even more preferably 0.93 or more.

[0035] When the ratio of Mooney stress relaxation at 100°C before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) is less than 1.05, for example, the rubber composition containing the hydrogenated random copolymer has excellent processability. From the same viewpoint, the ratio of Mooney stress relaxation at 100°C before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) is preferably 1.02 or less, more preferably 0.99 or less, and even more preferably 0.96 or less.

[0036] The method of controlling the 100°C Mooney stress relaxation ratio (after hydrogenation / before hydrogenation) of the random copolymer before and after hydrogenation to the above-mentioned specific range includes, for example, the composition ratio of aromatic vinyl compound and conjugated diene compound, the amount of bound styrene, the amount of 1,2-vinyl bond, the branching degree of the polymer after the addition of a modifier, the weight average molecular weight, the presence or absence of butadiene at the initiation terminal, etc. Specifically, for example, when the weight average molecular weight of the hydrogenated random copolymer is reduced, the 100°C Mooney stress relaxation ratio (after hydrogenation / before hydrogenation) of the random copolymer before and after hydrogenation tends to increase. In addition, for example, when the amount of bound styrene in the hydrogenated random copolymer is reduced, the 100°C Mooney stress relaxation ratio (after hydrogenation / before hydrogenation) of the random copolymer before and after hydrogenation tends to increase.

[0037] Specifically, for example, when the mass ratio of the aromatic vinyl monomer is 10 mass% and the amount of 1,2-vinyl bonds in the conjugated diene compound is 40%, the degree of branching of the modified polymer is 4-branched, and due to the presence of butadiene at the initiation terminal, the ratio of Mooney stress relaxation at 100°C before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) can be controlled to less than 1.05.

[0038] Furthermore, for example, when the proportion of the aromatic vinyl monomer is 20% by mass and the amount of 1,2-vinyl bonds in the conjugated diene compound is 20%, the ratio of Mooney stress relaxation at 100°C before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) can be controlled to 0.85 or more by setting the total hydrogenation rate to 65% or less, if that is the case.

[0039] As described above, when the polymer has a branched structure, the decrease in the Mooney stress relaxation value at 100°C of the random copolymer due to hydrogenation is reduced. In this case, the ratio of the Mooney stress relaxation values ​​at 100°C before and after hydrogenation of the random copolymer tends to be less dependent on the hydrogenation rate.

[0040] In this embodiment, the ratio of the Mooney stress relaxation at 100° C. before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) is measured by the method described in the Examples section below.

[0041] The larger the Mooney stress relaxation value, that is, the faster the material relaxes, the higher the viscosity and the lower the elasticity.Generally, hydrogenated polymers have low viscosity and dryness, so that crumbs tend to break into pieces without being consolidated, but the hydrogenated random copolymer obtained by the manufacturing method of the present embodiment has a small change in Mooney stress relaxation before and after hydrogenation, so that the viscosity is not impaired by hydrogenation.For example, when producing crumbs of hydrogenated random copolymers, the particle size of crumbs becomes large in the steam stripping process, and it is excellent in production stability, and it is also presumed that, for example, even when it is made into a rubber composition, even at high viscosity, the processability is not impaired.

[0042] In the method for producing the hydrogenated random copolymer of this embodiment, in the hydrogenation reaction step, the Mooney stress relaxation value at 100° C. of the resulting hydrogenated random copolymer is preferably 0.2 to 0.6, more preferably 0.3 to 0.55, and even more preferably 0.4 to 0.5. When the Mooney stress relaxation value at 100° C. of the resulting hydrogenated random copolymer is in the above range, the copolymer has a moderately branched structure, which tends to suppress the decrease in Mooney stress relaxation due to hydrogenation and makes it easier to control the stress relaxation ratio within a certain range.

[0043] In the present embodiment, the Mooney stress relaxation at 100° C. of the hydrogenated random copolymer is measured by the method described in the Examples below.

[0044] In the method for producing the hydrogenated random copolymer of this embodiment, the hydrogenation rate of the resulting hydrogenated random copolymer (proportion of hydrogenated relative to the conjugated diene portion, hereinafter also referred to as "total hydrogenation rate") is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more from the viewpoint of crosslinkability in the hydrogenation reaction step. In addition, in the method for producing the hydrogenated random copolymer of this embodiment, the total hydrogenation rate of the resulting hydrogenated random copolymer is preferably 95% or less, more preferably 90% or less, and even more preferably 85% or less from the viewpoint of crosslinkability in the hydrogenation reaction step.

[0045] In this embodiment, the total hydrogenation rate of the hydrogenated random copolymer is 1 It can be calculated from the spectral reduction rate of the unsaturated bond part of the spectrum obtained by measuring H-NMR. Specifically, it can be measured by the method described in the Examples below.

[0046] The hydrogenated random copolymer obtained by the manufacturing method of this embodiment has an aromatic portion (structural unit based on an aromatic vinyl compound) content of preferably 10 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more from the viewpoint of wet grip performance, and preferably 60 mass% or less, more preferably 50 mass% or less from the viewpoint of fuel economy.

[0047] In the present embodiment, the content of the aromatic moiety in the hydrogenated random copolymer is measured by the method described in the examples described later.

[0048] The weight average molecular weight (Mw) of the hydrogenated random copolymer obtained by the production method of this embodiment is preferably 400,000 or more and 1,100,000 or less. The weight average molecular weight (Mw) of the hydrogenated random copolymer obtained by the production method of this embodiment is preferably 400,000 or more, more preferably 450,000 or more, and even more preferably 500,000 or more from the viewpoint of abrasion resistance when the hydrogenated random copolymer is used in a tire composition, and is preferably 1,100,000 or less, more preferably 1,050,000 or less, and even more preferably 1,000,000 or less from the viewpoint of Mooney viscosity of the hydrogenated random copolymer.

[0049] The weight average molecular weight of the hydrogenated random copolymer can be controlled within the above-mentioned range by adjusting the polymerization conditions, such as the amount of monomer added in the polymerization step, the polymerization time, and the polymerization temperature.

[0050] The molecular weight distribution (Mw / Mn) of the hydrogenated random copolymer obtained by the production method of this embodiment is preferably 1.0 or more and 1.5 or less.

[0051] The molecular weight distribution (Mw / Mn) of the hydrogenated random copolymer obtained by the production method of the present embodiment is, for example, from the viewpoint of fuel efficiency when the hydrogenated random copolymer is used in a tire composition, preferably 1.0 or more, more preferably 1.1 or more, and even more preferably 1.2 or more, and from the viewpoint of the Mooney viscosity of the hydrogenated random copolymer, preferably 1.5 or less, more preferably 1.4 or less, and even more preferably 1.3 or less.

[0052] In the present embodiment, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the hydrogenated random copolymer are measured by the method described in the examples described below.

[0053] (Method for Producing Hydrogenated Random Copolymer) (Polymerization method) In the method for producing the hydrogenated random copolymer of the present embodiment, the polymerization method in the polymerization step is not particularly limited, and any of solution polymerization, gas phase polymerization, and bulk polymerization can be used, but from the viewpoint of commercial production, solution polymerization is particularly preferred. The polymerization form may be either batch or continuous.

[0054] When the solution polymerization method is used, the monomer concentration in the solution is preferably 5% by mass or more, more preferably 10% by mass or more. When the monomer concentration in the solution is 5% by mass or more, the amount of the obtained copolymer increases, and the cost tends to be low. In addition, the monomer concentration in the solution is preferably 50% by mass or less, more preferably 30% by mass or less. When the monomer concentration in the solution is 50% by mass or less, the solution viscosity is low, which makes stirring easy and tends to facilitate polymerization.

[0055] (Polymerization initiator) In this embodiment, when anionic polymerization is performed in the polymerization step, the polymerization initiator is not particularly limited, but an organic lithium compound is preferably used. As the organic lithium compound, those having an alkyl group having 2 to 20 carbon atoms are preferred, such as ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, tert-octyl lithium, n-decyl lithium, phenyl lithium, 2-naphthyl lithium, 2-butyl-phenyl lithium, 4-phenyl-butyl lithium, cyclohexyl lithium, cyclopentyl lithium, and the reaction product of diisopropenylbenzene and butyl lithium, among which n-butyl lithium or sec-butyl lithium is preferred from the viewpoints of availability, safety, and the like.

[0056] (Polymerization Method) In the present embodiment, the method for producing a random copolymer using a polymerization initiator in the polymerization step is not particularly limited, and any conventionally known method can be used.

[0057] Specifically, in an organic solvent inert to the reaction, for example, a hydrocarbon solvent such as an aliphatic, alicyclic, or aromatic hydrocarbon compound, styrene, 1,3-butadiene, or the like is polymerized using, for example, butyllithium as a polymerization initiator, and optionally in the presence of a randomizer, to obtain the desired random copolymer.

[0058] In order to control the Mooney stress relaxation at 100°C after hydrogenation of the random copolymer, it is preferable to start with butadiene homopolymerization in the presence of styrene and 1,3-butadiene in the absence of a randomizer, and then add a randomizer to carry out copolymerization. This produces a butadiene block at the initiation terminal, and the presence of a butadiene block with low cohesive strength at the easily movable chain terminal reduces entanglement of the polymer chain, accelerating relaxation, and thus the ratio of the Mooney stress relaxation at 100°C before and after hydrogenation of the random copolymer (after hydrogenation / before hydrogenation) is controlled within a predetermined range.

[0059] Adding butadiene before the completion of the polymerization reaction increases the number of living polymer chains whose chain ends are butadienyl anions, improving the reactivity in the modification step described below, so it is preferable to add butadiene. The amount of butadiene added is preferably 2% or more and less than 25% of the total monomer amount. The addition is preferably performed such that the monomer conversion rate is 90% or more and less than 100%.

[0060] (Hydrocarbon solvents) In this embodiment, the hydrocarbon solvent used in the polymerization step is preferably one having 3 to 8 carbon atoms, and specifically, although not particularly limited, examples thereof include propane, n-butane, isobutane, n-pentane, isopentane, n-hexane, cyclohexane, propene, 1-butene, isobutene, trans-2-butene, cis-2-butene, 1-pentene, 2-pentene, 1-hexene, 2-hexene, benzene, toluene, xylene, ethylbenzene, etc. These may be used alone or in combination of two or more.

[0061] (Randomizer in anionic polymerization) The randomizer is a compound that has the effect of controlling the microstructure of the conjugated diene portion in a random copolymer, for example, increasing the 1,2-bond in butadiene and the 3,4-bond in isoprene, or controlling the composition distribution of the monomer unit in a random copolymer, for example, randomizing the styrene unit and the butadiene unit in a styrene-butadiene copolymer. There is no particular limitation on this randomizer, and any of the known compounds that have been generally used as randomizers in the past can be used. Specific examples of the randomizer include, but are not limited to, ethers such as dimethoxybenzene, tetrahydrofuran, dimethoxyethane, diethylene glycol dibutyl ether, diethylene glycol dimethyl ether, 2,2-di(2-tetrahydrofuryl)propane, triethylamine, pyridine, N-methylmorpholine, N,N,N',N'-tetramethylethylenediamine, and 1,2-dipiperidinoethane, and tertiary amines. In addition, specifically, but not limited to, for example, potassium salts such as potassium-t-amylate and potassium-t-butoxide, and sodium salts such as sodium-t-amylate can be used. These randomizers may be used alone or in combination of two or more. The amount of the randomizer used is preferably 0.01 molar equivalents or more, more preferably 0.05 molar equivalents or more, per mole of the organolithium compound. When the amount of the randomizer used is 0.01 molar equivalents or more, the addition effect is sufficiently obtained, and randomization tends to be easy. The amount of the randomizer used is preferably 1000 molar equivalents or less, more preferably 500 molar equivalents or less, per mole of the organolithium compound. When the amount of the randomizer used is 1000 molar equivalents or less, a large change in the reaction rate of the monomer is suppressed, and randomization tends to be easy.

[0062] (Reaction temperature) In this embodiment, the reaction temperature during the polymerization step is not particularly limited as long as the reaction proceeds suitably, but is usually preferably from -10°C to 100°C, and more preferably from 25°C to 70°C.

[0063] (Denaturation process) The method for producing the hydrogenated random copolymer of this embodiment preferably further includes a modification step of reacting the polymer obtained in the polymerization step with a modifying agent.

[0064] For example, a functional group that interacts with silica can be introduced into the polymerization end terminal of the copolymer by reacting the active end of the copolymer obtained by the polymerization step with a compound having a functional group that interacts with silica. This results in a copolymer with a modified polymerization end terminal. In this embodiment, the term "end" refers to a portion other than the structure derived from the monomer having a carbon-carbon double bond that is present at the end of the molecular chain.

[0065] The copolymer used in the modification reaction (hereinafter also referred to as terminal modification reaction) may have an unmodified or modified polymerization initiation terminal as long as it has an active terminal. In addition, the compound to be reacted with the active terminal of the copolymer is not particularly limited as long as it has a functional group that interacts with silica and can react with the polymerization active terminal. As a specific method for introducing a terminal modifying agent, a method using a terminal modifying agent containing a tin atom or a nitrogen atom is preferred, and a method using a terminal modifying agent containing a nitrogen atom is more preferred.

[0066] In the case of nitrogen modification, it is possible to measure the modification rate using columns with different nitrogen adsorption properties, so nitrogen modification is suitable when specifying the modification rate, and nitrogen modification is a preferred embodiment from the viewpoint of fuel economy and the like when the polymer is used as a tire tread.

[0067] As the terminal modifier, a bifunctional or higher functional modifier that gives a polymer a branched structure after reaction is preferred, and a nitrogen-containing alkoxysilane compound is more preferred from the standpoint of fuel economy when used in a tire tread.

[0068] Preferred examples of the nitrogen-containing alkoxysilane compound include 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza-2-silacycloheptane, 2,2-dimethoxy-1-(3-dimethoxymethyl)-1-aza-2-silacyclopentane, and 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane. 2-methoxy,2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy,2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy,2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, and 2-ethoxy,2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane. -ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, and tris(4-trimethoxysilylbutyl)amine, tetrakis[3-(2,2-dimethoxy-1-aza-2-silacyclopentane], -silacyclopentane)propyl]-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-bisaminomethylcyclohexane, and N1-(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N1-methyl-N3-(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N3-(3-(trimethoxysilyl)propyl)-1,3-propanediamine.

[0069] The terminal modification reaction can be carried out, for example, as a solution reaction. This solution reaction may be carried out using a solution containing unreacted monomers after the end of the polymerization reaction in the polymerization step, or may be carried out after isolating the copolymer contained in the solution and dissolving it in a suitable solvent such as cyclohexane. The terminal modification reaction may be carried out using either a batch system or a continuous system.

[0070] In this case, the method of adding the terminal modifying agent is not particularly limited, and examples thereof include a method of adding the agent all at once, a method of adding the agent in portions, a method of adding the agent continuously, and the like.

[0071] The amount of the compound used in the terminal modification reaction may be appropriately set depending on the type of compound used in the reaction, but is preferably 0.4 molar equivalents or more, more preferably 0.7 molar equivalents or more, relative to the metal atom involved in the polymerization reaction of the polymerization initiator. By setting the amount to 0.4 molar equivalents or more, the modification reaction can be sufficiently advanced, and the ratio of the Mooney stress relaxation at 100°C before and after the hydrogenation of the random copolymer can be controlled.

[0072] The temperature of the terminal modification reaction is usually preferably the same as the reaction temperature in the polymerization step, and is preferably -20 to 150°C, more preferably 0 to 120°C, and particularly preferably 20 to 100°C. If the temperature of the terminal modification reaction is equal to or higher than the lower limit, the viscosity of the modified copolymer tends to decrease. On the other hand, if the temperature of the terminal modification reaction is equal to or lower than the upper limit, the polymerization active terminals are less likely to be deactivated.

[0073] The reaction time for the terminal modification reaction is preferably 1 minute to 5 hours, and more preferably 2 minutes to 1 hour.

[0074] (Reaction stopped) Anionic polymerization can be terminated by adding a reaction terminator commonly used in this field. Such reaction terminators are not particularly limited, but examples thereof include polar solvents having active protons such as alcohols such as methanol, ethanol, isopropanol, and acetic acid, and mixtures thereof, or mixtures of such polar solvents with non-polar solvents such as hexane and cyclohexane. The amount of reaction terminator added is usually sufficient to be about the same molar amount or about twice the molar amount of the anionic polymerization initiator.

[0075] (Hydrogenation Method) When producing a hydrogenated random copolymer by hydrogenation, the hydrogenation method and reaction conditions are not particularly limited, and hydrogenation may be performed by a known method and under known conditions. Usually, hydrogenation is preferably performed at 20 to 150°C under a hydrogen pressure of 0.1 to 10 MPa in the presence of a hydrogenation catalyst. The hydrogenation rate of the hydrogenated random copolymer can be selected arbitrarily by changing the amount of the hydrogenation catalyst, the hydrogen pressure during the hydrogenation reaction, the reaction time, etc. As the hydrogenation catalyst used in the hydrogenation reaction step, usually, a compound containing any of metals in Groups 4 to 11 of the Periodic Table can be used. Specifically, although not particularly limited, for example, a compound containing Ti, V, Co, Ni, Zr, Ru, Rh, Pd, Hf, Re, or Pt atoms can be used as the hydrogenation catalyst. More specific examples of the hydrogenation catalyst include, but are not limited to, metallocene compounds of Ti, Zr, Hf, Co, Ni, Pd, Pt, Ru, Rh, Re, etc.; supported heterogeneous catalysts in which a metal such as Pd, Ni, Pt, Rh, Ru, etc. is supported on a support such as carbon, silica, alumina, diatomaceous earth, etc.; homogeneous Ziegler type catalysts in which an organic salt or acetylacetone salt of a metal element such as Ni or Co is combined with a reducing agent such as organoaluminum; organometallic compounds or complexes of Ru, Rh, etc.; fullerenes and carbon nanotubes that have absorbed hydrogen; and the like.

[0076] Among these, metallocene compounds containing any one of Ti, Zr, Hf, Co, and Ni are preferred because they can undergo hydrogenation in an inert organic solvent in a homogeneous system.Moreover, metallocene compounds containing any one of Ti, Zr, and Hf are preferred.The hydrogenation catalysts may be used alone or in combination of two or more.

[0077] In the present embodiment, a preferred method for obtaining a hydrogenated random copolymer is to carry out solution polymerization, and then subject the resulting polymer solution to a modification treatment as is, and then, if necessary, to a hydrogenation step.

[0078] [Crumb manufacturing method] The method for producing crumbs in this embodiment is as follows: a polymerization step of polymerizing an aromatic vinyl compound and a conjugated diene compound in a solvent to obtain a polymer solution; a hydrogenation reaction step of adding hydrogen to the obtained polymer solution to perform a hydrogenation reaction to obtain a hydrogenated random copolymer solution; and removing the solvent from the obtained hydrogenated random copolymer solution to obtain hydrogenated random copolymer crumbs having a median diameter (D50) of 6 mm or more and less than 15 mm. In the hydrogenation reaction step, the Mooney stress relaxation at 100°C of the resulting hydrogenated random copolymer is 0.85 or more and less than 1.05 relative to the Mooney stress relaxation at 100°C of the polymer before hydrogenation; In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100° C. of 80 or more and 200 or less.

[0079] In the method for producing crumbs in this embodiment, the method for obtaining the hydrogenated random copolymer solution can be the same as the method described above in [Method for producing hydrogenated random copolymer].

[0080] The method for removing the solvent from the hydrogenated random copolymer solution is not particularly limited as long as it is a method capable of obtaining hydrogenated random copolymer crumbs having a median diameter (D50) of 6 mm or more and less than 15 mm. Examples of the method include known solvent removal methods such as steam stripping, and methods performed by drying operations such as heat treatment using a dehydrating extruder, a drying extruder, or a conveyor.

[0081] (Median diameter of crumb (D50)) The average particle size of the crumb obtained by removing the solvent from the hydrogenated random copolymer solution, for example, the average particle size of the crumb obtained in the steam stripping process, affects the drying ability in the subsequent dehydration extrusion process, drying extrusion process, and drying conveyor process. If the average particle size of the crumb is not too large, for example, the dehydration efficiency in the drying conveyor increases, and the moisture content in the product bale can be reduced. On the other hand, if the average particle size of the crumb is not too small, for example, sufficient shear pressure is applied in the dehydration extruder or drying extruder, so that the dehydration efficiency increases and the moisture content in the product bale can be reduced.

[0082] For example, when a steam stripping step is performed, from the viewpoint of preventing the average particle size of the crumbs from becoming too large, the steam stripping temperature is, for example, preferably 70° C. or higher, more preferably 80° C. or higher, and even more preferably 90° C. or higher. From the viewpoint of the amount of steam used, the steam stripping temperature is preferably 110° C. or lower, more preferably 100° C. or lower, and even more preferably 95° C. or lower.

[0083] When the subsequent dehydration extrusion step and drying extrusion step are carried out, the preferred rotation speed and blade shape of the extruder also depend on the shape of the tank, and therefore it is preferable to set them taking the shape into consideration.

[0084] The average particle size of the crumbs can be discussed in terms of the particle size distribution of the crumbs, and the median diameter of the crumbs (D50) in particular is an important value for the drying process.

[0085] From the viewpoint of crumb transport efficiency, the median diameter (D50) of crumbs of the hydrogenated random copolymer is 6.0 mm or more, preferably 8.0 mm or more, more preferably 8.5 mm or more, and further preferably 9.0 mm or more.

[0086] From the viewpoint of crumb dehydration efficiency, the median diameter (D50) of crumbs of the hydrogenated random copolymer is less than 15 mm, preferably 12 mm or less, more preferably 11 mm or less, and further preferably 10 mm or less.

[0087] In this embodiment, the median diameter (D50) of the crumbs is measured by the method described in the Examples below.

[0088] For example, the concentration of the crumbs dispersed in the water obtained in the steam stripping process is preferably 0.1 to 20 mass%, more preferably 0.5 to 15 mass%, and even more preferably 1 to 10 mass% (ratio to the water during steam stripping).Within this range, crumbs having a good particle size can be obtained without causing operational problems.

[0089] [How the veil is manufactured] The method for producing a veil according to the present embodiment includes the steps of obtaining crumbs by the above-mentioned method for producing crumbs, and compressing the resulting crumb to obtain a bale.

[0090] The method for compressing the crumbs is not particularly limited, but may be, for example, a method of compressing the crumbs using a bale forming machine.

[0091] The compression pressure during bale molding is preferably 3 to 30 MPa, more preferably 10 to 20 MPa. When the compression pressure during bale molding is 30 MPa or less, the device can be designed compactly and the installation efficiency is good, while when the compression pressure during bale molding is 3 MPa or more, the bale moldability is good. When the bale moldability is good, the bale surface is smooth, there is no peeling of the polymer after the molding process, and expansion after molding tends to be suppressed.

[0092] The temperature of the crumbs of the hydrogenated random copolymer during bale molding is preferably 30 to 120° C., and more preferably 50 to 100° C. from the viewpoints of reducing residual solvent and suppressing thermal degradation. When the temperature of the crumbs of the hydrogenated random copolymer during bale molding is 30° C. or higher, the bale is easily molded, and when the temperature of the crumbs of the hydrogenated random copolymer during bale molding is 120° C. or lower, gel formation due to thermal degradation after bale molding is suppressed, which is preferable.

[0093] If the molecular weight of the hydrogenated random copolymer and the composition of the process oil are the same, the higher the temperature and pressure during bale molding, the smaller the specific surface area of ​​the bale.

[0094] The pressure retention time during compression is preferably 3 to 30 seconds, more preferably 5 to 20 seconds. When the pressure retention time during compression is 30 seconds or less, production efficiency is good, and when it is 5 seconds or more, moldability is good.

[0095] [Manufacturing method of pneumatic tires] The method for manufacturing a pneumatic tire according to the present embodiment includes the steps of: obtaining a hydrogenated random copolymer by the above-mentioned method for producing a hydrogenated random copolymer; a step of mixing the obtained hydrogenated random copolymer with a plasticizer component and a filler component to obtain a rubber composition; and a step of molding the obtained rubber composition to obtain a pneumatic tire.

[0096] The rubber composition contains, as a rubber component, a hydrogenated random copolymer obtained by the above-mentioned method for producing a hydrogenated random copolymer. In addition to the above-mentioned hydrogenated random copolymer, any other rubber commonly used in general rubber compositions for tires can be used, and specific examples include, but are not limited to, natural rubber (NR), isoprene rubber (IR), styrene butadiene rubber (SBR), butadiene rubber (BR), etc. These may be used alone or in combination of two or more.

[0097] In the rubber composition, the content of the filler component (A) and the content of the plasticizer component (B) are not particularly limited, and the content of the filler component is preferably 20 to 50 mass%, and the content of the plasticizer component is preferably 10 to 40 mass%, based on 100 mass% of the entire rubber composition.

[0098] The filler component is compounded in the rubber composition for the purpose of reinforcing the rubber, and is not particularly limited, and examples thereof include white fillers (inorganic fillers) such as silica, calcium carbonate, mica, aluminum hydroxide, magnesium oxide, magnesium hydroxide, clay, talc, alumina, titanium oxide, and mica, and carbon black. These may be used alone or in combination of two or more. Among them, silica and carbon black are preferred, and their combination is more preferred.

[0099] The silica is not particularly limited, and examples thereof include dry process silica (anhydrous silica) and wet process silica (hydrated silica), with wet process silica being preferred because it contains many silanol groups.

[0100] From the viewpoint of wear resistance, the nitrogen adsorption specific surface area (N2SA) of silica is preferably 60 m 2 / g or more, more preferably 120m 2 / g or more, and from the viewpoint of fuel economy, it is preferably 300m 2 / g or less, more preferably 200m 2 / g or less.

[0101] The nitrogen adsorption specific surface area of ​​silica is a value measured by the BET method in accordance with ASTM D3037-81.

[0102] From the viewpoint of fuel economy, the content of silica is preferably 30 parts by mass or more, and more preferably 50 parts by mass or more, per 100 parts by mass of the rubber component, and from the viewpoint of Mooney viscosity, it is preferably 120 parts by mass or less, and more preferably 100 parts by mass or less.

[0103] The carbon black is not particularly limited, but examples thereof include furnace blacks (furnace carbon blacks) such as SAF, ISAF, HAF, MAF, FEF, SRF, GPF, APF, FF, CF, SCF, and ECF; acetylene blacks (acetylene carbon blacks); thermal blacks (thermal carbon blacks) such as FT and MT; channel blacks (channel carbon blacks) such as EPC, MPC, and CC; graphite, etc. These may be used alone or in combination of two or more.

[0104] The nitrogen adsorption specific surface area (N2SA) of carbon black is usually 5 to 200 m 2 / g, and from the viewpoint of abrasion resistance, preferably 50m 2 / g or more, more preferably 80m 2 / g or more, and from the viewpoint of fuel economy, it is preferably 150 m 2 / g or less, more preferably 120m 2 / g or less. The dibutyl phthalate (DBP) absorption of carbon black is usually 5 to 300 mL / 100 g, and preferably has a lower limit of 80 mL / 100 g and an upper limit of 180 mL / 100 g. The nitrogen adsorption specific surface area is measured according to ASTM D4820-93, and the DBP absorption is measured according to ASTM D2414-93.

[0105] The amount of carbon black is preferably 1 part by mass or more, and more preferably 3 parts by mass or more, per 100 parts by mass of the rubber component from the viewpoint of abrasion resistance, and is preferably 30 parts by mass or less, and more preferably 15 parts by mass or less, per 100 parts by mass of the rubber component from the viewpoint of fuel economy.

[0106] Silica is preferably used in combination with a silane coupling agent.As the silane coupling agent, a conventionally known one can be used, and is not particularly limited, but for example, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(3-triethoxysilylpropyl)trisulfide, bis(3-trimethoxysilylpropyl)trisulfide, bis(3-triethoxy ... Sulfide series such as 3-mercaptopropyl methacrylate monosulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-trimethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl benzothiazole tetrasulfide, 3-triethoxysilylpropyl methacrylate monosulfide, and 3-trimethoxysilylpropyl methacrylate monosulfide; Mercapto-based compounds such as vinyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, and 2-mercaptoethyltriethoxysilane; vinyl-based compounds such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based compounds such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, and 3-(2-aminoethyl)aminopropyltrimethoxysilane; γ-glycidoxy-based compounds such as γ-glycidoxy-based compounds; Examples of the silane coupling agent include glycidoxy-based agents such as propyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and γ-glycidoxypropylmethyldimethoxysilane, nitro-based agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane, and chloro-based agents such as 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 2-chloroethyltrimethoxysilane, and 2-chloroethyltriethoxysilane. The silane coupling agents may be used alone or in combination of two or more.Among these, from the viewpoints of the coupling effect of the silane coupling agent, processability, and cost, sulfide-based silane coupling agents are preferred, and bis(3-triethoxysilylpropyl)tetrasulfide and bis(3-triethoxysilylpropyl)disulfide are more preferred.

[0107] The content of the silane coupling agent is preferably 3 parts by mass or more, and more preferably 5 parts by mass or more, per 100 parts by mass of silica from the viewpoints of fuel economy and abrasion resistance, and is preferably 15 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of silica from the viewpoint of Mooney viscosity.

[0108] The plasticizer component is not particularly limited, but examples thereof include extender oil, resin, antioxidant, wax, stearic acid, vulcanization accelerator, etc. These may be used alone or in combination of two or more.

[0109] The extender oil is not particularly limited, but examples thereof include aromatic mineral oils (viscosity specific gravity constant (VGC value) 0.900 to 1.049), naphthenic mineral oils (VGC value 0.850 to 0.899), and paraffinic mineral oils (VGC value 0.790 to 0.849). The polycyclic aromatic content of the extender oil is preferably less than 3 mass%, more preferably less than 1 mass%. The polycyclic aromatic content is measured according to the British Petroleum Institute 346 / 92 method. The aromatic compound content (CA) of the extender oil is preferably 20 mass% or more. Two or more of these extender oils may be used in combination.

[0110] The amount of the extender oil is preferably 5 parts by mass or more, and more preferably 10 parts by mass or more, per 100 parts by mass of the rubber component from the viewpoint of Mooney viscosity, and is preferably 50 parts by mass or less, and more preferably 40 parts by mass or less, per 100 parts by mass of the rubber component from the viewpoint of fuel economy.

[0111] The resin is not particularly limited, but examples thereof include C5-based petroleum resin, C9-based petroleum resin, coumarone-indene resin, indene resin, phenol-based resin, copolymer of α-methylstyrene and / or styrene, etc. These may be used alone or in combination of two or more. Among them, coumarone-indene resin, phenol-based resin (particularly, terpene phenol resin), copolymer of α-methylstyrene and / or styrene are preferred, and copolymer of α-methylstyrene and styrene is more preferred.

[0112] From the viewpoint of wet grip performance, the resin content is preferably 1 part by mass or more, and more preferably 3 parts by mass or more, per 100 parts by mass of the rubber component, and from the viewpoint of fuel economy, the resin content is preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of the rubber component.

[0113] The antioxidant is not particularly limited, but examples thereof include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-phenyl-N'-isopropyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, Examples of the antioxidant include p-phenylenediamine antioxidants such as diamine; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. These may be used alone or in combination of two or more. Among them, p-phenylenediamine antioxidants are preferred, and N-phenyl-N'-isopropyl-p-phenylenediamine is more preferred. The content of the antioxidant is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component.

[0114] The wax is not particularly limited, but examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as vegetable wax and animal wax; and synthetic waxes such as polymers of ethylene, propylene, etc. These may be used alone or in combination of two or more. Among them, petroleum waxes are preferred, and paraffin wax is more preferred. The wax content is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component.

[0115] As the stearic acid, any conventionally known product can be used, and is not particularly limited. For example, products from NOF Corporation, NOF Corporation, Kao Corporation, Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., etc. can be used. These may be used alone or in combination of two or more. The content of stearic acid is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component.

[0116] The vulcanization accelerator is not particularly limited, but examples thereof include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, dibenzothiazyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram monosulfide and tetramethylthiuram disulfide; sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolylguanidine, and orthotolylbiguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide vulcanization accelerators are preferred, and N-cyclohexyl-2-benzothiazole sulfenamide is more preferred, because the effects of the present invention can be more suitably obtained. It is also preferred to use a guanidine vulcanization accelerator in combination. The content of the vulcanization accelerator is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component.

[0117] In addition to the above-mentioned components, the rubber composition may contain compounding agents conventionally used in the rubber industry, such as vulcanizing agents such as sulfur; vulcanization activators such as zinc oxide; organic peroxides; processing aids such as lubricants; and antioxidants.

[0118] The vulcanizing agent is not particularly limited, but sulfur can be preferably used. The content of sulfur is preferably 0.5 to 5 parts by mass, more preferably 1 to 3 parts by mass, based on 100 parts by mass of the rubber component. This makes it possible to more suitably obtain the effects of the present invention.

[0119] The rubber composition can be produced by a general method, i.e., by kneading the components in a Banbury mixer, kneader, open roll, or the like, and then vulcanizing the mixture.

[0120] In the method for producing a pneumatic tire of the present embodiment, a pneumatic tire can be obtained by molding the rubber composition, but the rubber composition can be used for applications other than pneumatic tires.

[0121] The rubber composition can be used for each component of a tire (tread, sidewall, carcass, belt, bead, clinch, chafer, etc.), and is particularly suitable for use as a tread. In the case of a two-layer tread, the tread is composed of a surface layer (cap tread) and an inner layer (base tread).

[0122] A multi-layered tread can be produced by laminating sheets into a predetermined shape, or by feeding the sheet into two or more extruders and forming two or more layers at the head outlet of the extruders.

[0123] (Method of molding rubber composition) In the manufacturing method of the pneumatic tire of this embodiment, the method of molding the rubber composition is not particularly limited, and a conventional method can be used. That is, the rubber composition containing the rubber component and, if necessary, the various compounding agents is extruded in the unvulcanized stage to match the shape of each tire component such as the tread, and molded together with other tire components in a conventional manner on a tire building machine to form an unvulcanized tire. The unvulcanized tire is heated and pressurized in the vulcanizer to obtain a pneumatic tire.

[0124] The pneumatic tire obtained by the manufacturing method of this embodiment is suitable for use as a passenger car tire, a truck / bus tire, a motorcycle tire, a racing tire, etc., and is particularly suitable for use as a passenger car tire. EXAMPLES

[0125] Hereinafter, the present embodiment will be described in more detail with reference to specific examples and comparative examples, but the present embodiment is not limited in any way to the following examples and comparative examples.

[0126] Various physical properties in the examples and comparative examples were measured by the methods shown below.

[0127] (Bound styrene content of random copolymer before hydrogenation) 100 mg of the sample was made into 100 mL of chloroform and dissolved to prepare a measurement sample. The amount of bound styrene (mass%) relative to 100 mass% of the sample random copolymer before hydrogenation was measured based on the amount of absorption of ultraviolet light by the phenyl group of styrene (near 254 nm) (measurement device: Shimadzu Corporation spectrophotometer "UV-2450").

[0128] (1,2-vinyl bond content in butadiene part of random copolymer before hydrogenation) 50 mg of the sample was dissolved in 10 mL of carbon disulfide to prepare a measurement sample. The infrared spectrum was recorded from 600 to 1000 cm using a solution cell. -1 The absorbance at a predetermined wave number was measured in the range of 100 nm to 150 nm, and the microstructure of the butadiene portion (Bd) in the random copolymer before hydrogenation (i.e., the amount of 1,2-vinyl bonds (mol%)) was calculated according to the formula of Hampton's method (method described in R.R. Hampton, Analytical Chemistry 21, 923 (1949)) (measuring device: Fourier transform infrared spectrophotometer "FT-IR230" manufactured by JASCO Corporation).

[0129] (Mooney Viscosity and Mooney Stress Relaxation) Using a Mooney viscometer (manufactured by Ueshima Seisakusho Co., Ltd., product name "VR1132"), the Mooney viscosity of the hydrogenated random copolymer, and the Mooney stress relaxation (relaxation rate) of the hydrogenated random copolymer and the polymer before hydrogenation were measured in accordance with JIS K6300 (ISO289-1) and ISO289-4. The measurement temperature was 100°C. First, the sample was preheated for 1 minute, and then the rotor was rotated at 2 rpm. The torque was measured after 4 minutes to determine the Mooney viscosity (ML (1+4)Thereafter, in the case where the hydrogenated random copolymer and the polymer before hydrogenation were used as the sample, the rotation of the rotor was immediately stopped, and the torque was recorded in Mooney units every 0.1 seconds for 1.6 to 5 seconds after the rotor was stopped, and the slope of the straight line obtained by plotting the torque versus time (seconds) logarithmically was determined, and the absolute value was taken as the Mooney stress relaxation (MSR).

[0130] (Total hydrogenation rate of hydrogenated random copolymer) In the production of hydrogenated random copolymers in the Examples and Comparative Examples described below, a large amount of methanol was added to the reaction solution after the hydrogenation reaction to precipitate and recover the conjugated diene polymer before hydrogenation and the hydrogenated conjugated diene polymer. The hydrogenated random copolymer was then extracted with acetone and vacuum dried. 1 The total hydrogenation rate of the hydrogenated random copolymer was measured using the sample for H-NMR measurement under the following conditions. (Measurement conditions) Measuring equipment: JNM-LA400 (JEOL) Solvent: Deuterated chloroform Measurement sample: Samples taken before and after hydrogenation of the polymer Sample concentration: 50mg / mL Observation frequency: 400MHz Chemical shift reference: TMS (tetramethylsilane) Pulse Delay: 2.904 seconds Number of scans: 64 Pulse width: 45° Measurement temperature: 26℃

[0131] (Weight average molecular weight Mw, number average molecular weight Mn, molecular weight distribution MWD (Mw / Mn)) A hydrogenated random copolymer was used as a sample, and a chromatogram was measured using a GPC measuring device with three columns packed with polystyrene gel. The weight average molecular weight (Mw) and number average molecular weight (Mn) were determined based on a calibration curve obtained using standard polystyrene. Tetrahydrofuran (hereinafter also referred to as "THF") was used as the eluent. The columns were a guard column manufactured by Tosoh Corporation under the trade name "TSKguardcolumn HHR-H" and a column manufactured by Tosoh Corporation under the trade name "TSKgel SuperMultipore HZ-H". An RI (differential refractive index) detector (manufactured by Tosoh Corporation under the trade name "HLC8020") was used under the conditions of an oven temperature of 40°C and a flow rate of THF in TEA (triethylamine) of 1.0 mL / min. 10 mg of the sample to be measured was dissolved in 20 mL of THF to prepare a measurement solution, and 200 μL of the measurement solution was injected into the GPC measuring device for measurement.

[0132] (Crumb manufacturing method) The hydrogenated random copolymer solution obtained by the method described in the examples and comparative examples below was subjected to steam stripping to remove the solvent, thereby obtaining crumbs of the hydrogenated random copolymer having a predetermined median diameter (D50). In this embodiment, the process of obtaining the crumbs is called "crumbing". The conditions of crumbing are as follows: Water temperature: 80℃ Water amount: 8kg Mixing tank: 300mm inner diameter, 300mm high mixing tank with impeller Agitator blades: 2 turbine blades Agitator rotation speed: 500 rpm Amount of polymer used for cracking: 200g Polymer solution addition rate to the Cramming tank: 7g / min

[0133] (Crum's D50 rating (productivity rating)) The crumb obtained by the above crumbing was sieved using a metal mesh sieve (JIS Z 8801-1:2000, manufactured by Okutani Metal Works, Ltd.) to separate the crumbs into crumbs corresponding to the opening sizes. The opening sizes of the metal mesh sieves used are shown below. 26.5mm, 22.1mm, 19.1mm, 15.9mm, 12.7mm, 11.1mm, 9.52mm, 7.93mm, 6.73mm, 4.75mm, 3.36mm, 0.50mm The weight of the crumbs on the sieve with each opening was measured, and the particle size of the crumbs when the weight accumulated from the smallest to the largest was 50% was calculated as the median diameter (D50). D50 was evaluated according to the following criteria. If the D50 of the crumbs is less than 15 mm, for example, when dehydrating the crumbs, the occurrence of bridges can be suppressed in the hopper at the inlet of the dehydrating extruder, improving productivity. On the other hand, if the D50 of the crumbs is 6 mm or more, for example, when dehydrating the crumbs, the shear is applied moderately in the dehydrating extruder, so the moisture content in the crumbs can be efficiently reduced, and as a result, the load on the drying extruder in the subsequent stage is reduced, and the drying time on the conveyor can be shortened, improving productivity. ○: 10 mm or more and less than 15 mm △: 6 mm or more and less than 10 mm ×: 15mm or more or less than 6mm

[0134] (Evaluation of processability and abrasion resistance) <Production of Rubber Composition> The hydrogenated random copolymer obtained by the method described in the Examples and Comparative Examples below, and the random copolymer obtained by the method described in the Reference Examples below, and each raw material other than sulfur and vulcanization accelerator were kneaded for 5 minutes under the condition of 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. according to the formulation shown in Table 1 to obtain a kneaded product. Next, the sulfur and vulcanization accelerator were added to the kneaded product obtained in the formulation shown in Table 1, and the mixture was kneaded for 5 minutes under the condition of 80°C using an open roll to obtain an unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized in a 0.5 mm thick mold at 170° C. for 20 minutes to obtain a vulcanized rubber composition.

[0135] [Table 1]

[0136] <Evaluation items and test methods> The unvulcanized rubber compositions and vulcanized rubber compositions thus obtained were subjected to the following evaluations.

[0137] (1) Processability The unvulcanized rubber composition was wound around a 6-inch open roll at 60° C., and the state of winding around the roll was visually observed, and the roll processability was evaluated using the following index. ◯: The film sticks to the roll from the beginning and wraps around the roll. The roll processability is extremely good. △: The material wraps around the roll to some extent from the beginning of the roll insertion. There are no major problems with roll processability. ×: Not sticky and does not wrap around a roll. Roll processing is difficult (sample is powder or granular).

[0138] (2) Abrasion resistance Using a Laboratory Abration and Skid Tester (LAT tester), the volume loss of each vulcanized rubber composition (crosslinked rubber) was measured under conditions of a load of 50 N, a speed of 20 km / h, and a slip angle of 5°. The measurement results were indexed based on the volume loss of each non-hydrogenated vulcanized rubber composition of each Example and Comparative Example being 100, and the abrasion resistance was evaluated using the following index. 〇: 110 or more compared to the non-hydrogenated reference example △: 105 or more and less than 110 compared to the non-hydrogenated reference example ×: Less than 105 compared to non-hydrogenated reference example For the samples with processability rated as ×, it was not possible to prepare a vulcanized rubber composition, and it was not possible to evaluate the abrasion resistance.

[0139] (Preparation of hydrogenation catalyst) In the examples and comparative examples described later, the hydrogenation catalyst used in preparing the hydrogenated random copolymer was prepared by the following method. A nitrogen-substituted reaction vessel was charged with 1 liter of dried and purified cyclohexane, and 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added. With sufficient stirring, an n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was allowed to react at room temperature for approximately 3 days to obtain a hydrogenation catalyst.

[0140] [Example 1] 25,800 g of cyclohexane, 430 g of styrene, and 2,980 g of 1,3-butadiene were charged into a nitrogen-purged autoclave reactor having an internal volume of 40 L. After adjusting the temperature of the reactor contents to 10° C., a cyclohexane solution containing 2.7 g of n-butyllithium was added to the reactor to initiate polymerization, and polymerization was carried out under adiabatic conditions. Five minutes after the start of polymerization, 4.65 g of 2,2-di(2-tetrahydrofuryl)propane was added to the reactor to continue polymerization. When the polymerization conversion reached 99%, 890 g of butadiene was added to the reactor, and polymerization was continued for another 5 minutes to obtain a reaction solution containing a polymer. Then, 2.74 g of 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was added as a modifier, and reacted with the active sites of the polymer for 30 minutes to obtain a random copolymer solution before hydrogenation. Here, as in Reference Example 1 described later, various physical properties such as Mooney stress relaxation at 100 ° C. of the random copolymer before hydrogenation were measured. The results are shown in Table 3. Next, hydrogenation reaction was carried out as follows so that the Mooney stress relaxation ratio at 100°C of the random copolymer before and after hydrogenation and the Mooney viscosity at 100°C of the resulting hydrogenated random copolymer were within a predetermined range. Specifically, the reaction solution was first heated to 80°C and hydrogen was introduced into the reactor. Then, the hydrogenation catalyst prepared as described above was added to the reactor in an amount of 60 ppm based on titanium relative to the amount of charged monomer, and hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C. After reaching a predetermined cumulative hydrogen flow rate, the reaction solution was returned to room temperature and pressure and withdrawn from the reactor to obtain a hydrogenated random copolymer solution. The hydrogenated random copolymer solution obtained was subjected to crumbing under the above-mentioned conditions to obtain crumbs of hydrogenated random copolymer 1. The D50 of the obtained crumbs was calculated by the above-mentioned method to evaluate the productivity. The evaluation results are shown in Table 2. After calculating the D50 of the crumbs, the crumbs were dried for 2 hours in a vacuum dryer heated to 90°C to obtain an analysis sample of hydrogenated random copolymer 1. The processability and abrasion resistance of the obtained hydrogenated random copolymer 1 were evaluated by the above-mentioned method. The evaluation results are shown in Table 2. The polymerization conditions and each physical property of hydrogenated random copolymer 1 are shown in Table 2.

[0141] [Examples 2 to 3] Hydrogenated random copolymers 2 and 3 were produced and evaluated in the same manner as in Example 1, except that the polymerization conditions were changed to those shown in Table 2. The evaluation results are shown in Table 2. The polymerization conditions and physical properties of hydrogenated random copolymers 2 and 3 are also shown in Table 2.

[0142] [Example 4] Hydrogenated random copolymer 4 was produced and evaluated in the same manner as in Example 1, except that the amount of N,N-bis(trimethylsilyl)aminopropyltrimethoxysilane used as the modifier was changed to 6.38 g, and the polymerization conditions were changed to those shown in Table 2. The evaluation results are shown in Table 2. The polymerization conditions and physical properties of hydrogenated random copolymer 4 are also shown in Table 2.

[0143] [Example 5] Hydrogenated random copolymer 5 was produced and evaluated in the same manner as in Example 1, except that the amount of tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine as the modifier was changed to 2.62 g and the polymerization conditions were changed to those shown in Table 2. The evaluation results are shown in Table 2. The polymerization conditions and physical properties of hydrogenated random copolymer 5 are also shown in Table 2.

[0144] [ Reference Example 16 ] Hydrogenated random copolymer 6 was produced and evaluated in the same manner as in Example 1, except that the amount of N1-(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N1,N3,N3-tris(3-(trimethoxysilyl)propyl)propane-1,3-diamine used as the modifier was changed to 1.42 g, and the polymerization conditions were changed to those shown in Table 2. The evaluation results are shown in Table 2. The polymerization conditions and physical properties of hydrogenated random copolymer 6 are also shown in Table 2.

[0145] [Example 7] Hydrogenated random copolymer 7 was produced and evaluated in the same manner as in Example 2, except that the amount of tin tetrachloride used as the modifier was changed to 1.19 g. The evaluation results are shown in Table 2. The polymerization conditions and physical properties of hydrogenated random copolymer 7 are also shown in Table 2.

[0146] [ Reference Example 17 ] Hydrogenated random copolymer 8 was produced and evaluated in the same manner as in Example 6, except that the hydrogenation rate was 20%. The evaluation results are shown in Table 2. The polymerization conditions and physical properties of hydrogenated random copolymer 8 are also shown in Table 2.

[0147] [Comparative Examples 1 to 7] Hydrogenated random copolymers 9 to 15 were produced and evaluated in the same manner as in Example 1, except that the polymerization conditions were changed to those shown in Table 2. The evaluation results are shown in Table 2. The polymerization conditions and physical properties of hydrogenated random copolymers 9 to 15 are also shown in Table 2.

[0148] [Table 2]

[0149] [Reference examples 1~15] Example 1 5.7. Reference Examples 16~17 The polymerization solutions before hydrogenation of the comparative examples 1 to 7 were subjected to the above-mentioned method to produce random copolymers 1 to 15. The polymerization conditions and physical properties of the random copolymers 1 to 15 are shown in Table 3.

[0150] [Table 3]

[0151] From the results in Table 2, it was found that the hydrogenated random copolymers produced in the Examples have improved crumb particle size when crumbs are produced, and therefore have superior productivity compared to the hydrogenated random copolymers produced in the Comparative Examples. Furthermore, from the results in Table 2, it was found that the hydrogenated random copolymers produced in the Examples have improved processability and abrasion resistance, for example, when used as rubber compositions for tires, compared to the hydrogenated random copolymers produced in the Comparative Examples.

[0152] As described above, it has been found that the use of the hydrogenated random copolymer obtained by the production method of the present invention improves the crumb particle size, leading to excellent productivity, and further to improved processability and abrasion resistance, for example, when made into a rubber composition for tires. In other words, it has been made clear that the present invention can provide a hydrogenated random copolymer that is excellent in productivity and processability, and further to improved abrasion resistance, for example, when made into a tire tread. [Industrial Applicability]

[0153] INDUSTRIAL APPLICABILITY The present invention can provide a hydrogenated random copolymer that can be used as a raw material for tire treads, etc., and has industrial applicability.

Claims

1. a polymerization step of polymerizing an aromatic vinyl compound and a conjugated diene compound to obtain a polymer; and a hydrogenation reaction step of adding hydrogen to the obtained polymer to obtain a hydrogenated random copolymer, In the hydrogenation reaction step, the Mooney stress relaxation at 100°C of the resulting hydrogenated random copolymer is 0.85 or more and less than 1.05 relative to the Mooney stress relaxation at 100°C of the polymer before hydrogenation, In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100° C. of 80 or more and 200 or less, A method for producing a hydrogenated random copolymer, wherein in the hydrogenation reaction step, a total hydrogenation rate of the obtained hydrogenated random copolymer is 60% or more.

2. 2. The method for producing a hydrogenated random copolymer according to claim 1, further comprising a step of reacting the polymer obtained in the polymerization step with a coupling agent and / or a modifier.

3. 3. The method for producing a hydrogenated random copolymer according to claim 1, wherein in the hydrogenation reaction step, a total hydrogenation rate of the obtained hydrogenated random copolymer is 60% or more and 95% or less.

4. The method for producing a hydrogenated random copolymer according to any one of claims 1 to 3, wherein the hydrogenated random copolymer obtained in the hydrogenation reaction step has a Mooney stress relaxation at 100°C of 0.2 to 0.

6.

5. a polymerization step of polymerizing an aromatic vinyl compound and a conjugated diene compound in a solvent to obtain a polymer solution; a hydrogenation reaction step of adding hydrogen to the obtained polymer solution to perform a hydrogenation reaction to obtain a hydrogenated random copolymer solution; and removing the solvent from the obtained hydrogenated random copolymer solution to obtain hydrogenated random copolymer crumbs having a median diameter (D50) of 6 mm or more and less than 15 mm. In the hydrogenation reaction step, the Mooney stress relaxation at 100°C of the resulting hydrogenated random copolymer is 0.85 or more and less than 1.05 relative to the Mooney stress relaxation at 100°C of the polymer before hydrogenation, In the hydrogenation reaction step, the hydrogenated random copolymer obtained has a Mooney viscosity at 100° C. of 80 or more and 200 or less, The method for producing crumbs, wherein the total hydrogenation rate of the resulting hydrogenated random copolymer is 60% or more in the hydrogenation reaction step.

6. Obtaining crumbs by the method according to claim 5; and compressing the resulting crumb to obtain a bale.

7. A step of obtaining a hydrogenated random copolymer by the production method according to any one of claims 1 to 4; a step of mixing the obtained hydrogenated random copolymer with a plasticizer component and a filler component to obtain a rubber composition; and a step of molding the obtained rubber composition to obtain a pneumatic tire.

Citation Information

Patent Citations

  • Thermal color printer

    JP1985004081A

  • Production of block copolymer

    JP1989056713A

  • Process for obtaining butadiene-styrene copolymers by emulsion polymerization; rheology modifying agent for copolymer; rubber composition; gum base; chewing gum; and bubble gum

    WO2008019461A1

  • Branched conjugated diene-aromatic vinyl copolymer and method for producing same

    WO2010116991A1

  • Process for producing modified conjugated diene polymer, modified conjugated diene polymer, and composition of modified conjugated diene polymer

    WO2011129425A1